Enhancing Islamic Moral Understanding and Critical Thinking through an Augmented Reality Qur’anic Storytelling Platform in Primary Education - RA. Thoyyiba Firdaus; Iwan Kuswandi; M Ridwan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Islamic Religious Education (IRE) aims not only to impart religious knowledge but also to cultivate students’ moral understanding and critical thinking. However, conventional Qur’anic storytelling methods often fall short in engaging students cognitively and ethically. This study investigates the effectiveness of an Augmented Reality (AR)–based Qur’anic storytelling platform in enhancing Islamic moral understanding and critical thinking among primary school students. A quasi-experimental pretest–posttest non-equivalent control group design was used with 80 sixth-grade students in Indonesia, divided equally into experimental and control groups. The experimental group received instruction through the AR-based Qur’anic storytelling platform, while the control group experienced conventional teacher-led narrative instruction. A 30-item validated instrument assessed Islamic moral understanding and critical thinking before and after the intervention. Posttest scores showed significantly higher gains in the experimental group for both Islamic moral understanding (M = 82.90) and critical thinking (M = 80.25), compared to the control group (M = 68.75 and M = 65.90, respectively). Independent t-tests confirmed these differences were statistically significant (p .001). Large effect sizes (Cohen’s d 1.90) were observed, indicating strong practical impact. Findings suggest that AR-enhanced storytelling can transform traditional moral instruction by fostering deeper engagement, reflective judgment, and higher-order thinking. This pedagogically guided use of AR offers promising implications for values-based education and supports the integration of immersive technologies into Islamic Religious Education curricula.